Dampak Pembelajaran Portofolio Terhadap Prestasi Akademik Siswa Pada Pelajaran IPS - Ari Saputra; Taufan Iswandi (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The aim of this research is to find out how the portfolio learning approach influences student learning outcomes in the Social Sciences class at MTS Putri Bale Dakwah during the 2023-2024 academic year. Class members were used as research subjects in this experimental research. After data collection and processing, the researcher calculated an average score of 82 for the experimental group and 64 for the control group. The t-test formula is used in research to test hypotheses. The hypothesis was approved with a research t-value of 6.02 and t-table at a significance level of 5% or 1.684. This shows that the learning portfolio approach has an impact on student learning outcomes in social studies learning at MTs Putri Bale Dakwah.